A Network of Argumentation Schemes and Critical Questions - Pyon, Sung-Jun; Ri, Yong-Sok (Informal Logic)

(untitled) (Informal Logic, 2022)
In this paper, we devise a network that consists of argumentation schemes and critical questions that participants in debates can use to easily construct arguments that attack or support former arguments. As a prototype, we build a potential network of argumentation schemes and critical questions with a practical reasoning scheme at its center. The usefulness of a NASCQ in constructing and reconstructing complex arguments and in formal argumentation is also explored along with argumentation more broadly.